The Assessment of SpondyloArthritis International Society (ASAS) Consensus-Based Expert Definition of Difficult-to-Manage, including Treatment-Refractory, Axial Spondyloarthritis - Poddubnyy, Denis (2025)
Publisher Copyright: © 2025 The Author(s)